A Systematic Literature Review of Brand Switching Behavior - Pratama, Ferdian Tomy; Haryanto, Budhi (Asian Journal of Management, Entrepreneurship and Social Science, 2025)
The article uses a systematic review literature that aims to summarize some research on brand switching behavior. This artike employs the PRISMA (Preferred Reporting Items for Systematic Review and Meta-Analyses) technique with the aid of UAKE's Watase program. Literature gathered throughout the previous ten years from 2014 to 2024 was analysed using the Watase UAKE program to obtain article extraction in the form of article information. The findings of the analysis suggest that 2023 is the year with the greatest relevant number of publications, with five articles published. An study published in 2019 by Information Technology & People and titled "The impacts of consumption values and relational advantages on smartphone brand switching behaviour" has 75 citations and was written by Wong, Kit Hong; Chang, Hsin Hsin; and Yeh, Chih Heng. This article is the most referenced article when compared to the collection of articles retrieved. The country that publishes the most publications on the topic of brand switching behavior is China with three articles. Keywords: Brand switching behavior